1993
DOI: 10.1126/science.8493557
|View full text |Cite
|
Sign up to set email alerts
|

GDNF: a Glial Cell Line-Derived Neurotrophic Factor for Midbrain Dopaminergic Neurons

Abstract: A potent neurotrophic factor that enhances survival of midbrain dopaminergic neurons was purified and cloned. Glial cell line-derived neurotrophic factor (GDNF) is a glycosylated, disulfide-bonded homodimer that is a distantly related member of the transforming growth factor-beta superfamily. In embryonic midbrain cultures, recombinant human GDNF promoted the survival and morphological differentiation of dopaminergic neurons and increased their high-affinity dopamine uptake. These effects were relatively speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,866
5
23

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,969 publications
(1,930 citation statements)
references
References 25 publications
36
1,866
5
23
Order By: Relevance
“…Glial derived neurotrophic factor (GDNF) is a potent neurotrophic factor that is crucial to the development, survival, and outgrowth of DA neurons (Airaksinen and Saarma, 2002;Lin et al, 1993), and so it is a good candidate for protecting and maintaining grafted fetal DA neurons in the host brain. GDNF is highly expressed in the developing rat striatum, yet its concentration is relatively low in the adult brain (Choi-Lundberg and Bohn, 1995;Schaar et al, 1993;Stromberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Glial derived neurotrophic factor (GDNF) is a potent neurotrophic factor that is crucial to the development, survival, and outgrowth of DA neurons (Airaksinen and Saarma, 2002;Lin et al, 1993), and so it is a good candidate for protecting and maintaining grafted fetal DA neurons in the host brain. GDNF is highly expressed in the developing rat striatum, yet its concentration is relatively low in the adult brain (Choi-Lundberg and Bohn, 1995;Schaar et al, 1993;Stromberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…GDNF, its prototypical member, was isolated from a glial cell line due to its neurotrophic effects on cultured dopaminergic neurones [6]. Subsequent studies have shown that it can also act on other neuronal types (see [7]).…”
Section: Effects Of Gdnf In Vitromentioning
confidence: 99%
“…GDNF has been consistently shown to promote the survival and differentiation of dopaminergic neurones in vitro [6,9,10] and to protect these cells from the dopaminergic toxins, 1-methyl-4-phenylpyridinium ion (MPP+) and 6-hydroxydopamine (6-OHDA), [11][12][13]. GDNF treatment has also been reported to reduce apoptosis in dopaminergic neurones cultured from embryonic rat [14,15] and human [16] midbrain.…”
Section: Effects Of Gdnf In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we examined the capacity of adipose cells to secrete a transgene product, glial cell line-derived neurotrophic factor (GDNF), which is a potent neurotrophin capable of supporting neuron survival in culture. 14 We recently reported that a component of the viral latency promoter, latencyassociated transcript 2 (LAP2), provides long-term transgene expression in neurons. 15 Moreover, the activity of LAP2 can be enhanced when used in combination with a strong promoter such as the HCMV IE gene promoter (SH and WFG, unpublished data).…”
Section: Hsv-mediated Gdnf Expression From Adipose Cellsmentioning
confidence: 99%